A novel "caterpillar with eggs" mesostructured iron sulfide as an anode for a Li-ion battery displaying stable electrochemical performance. Issue 10 (11th January 2022) - Zhou, Ting; Wang, Yan; Zhu, Yajun; Han, Tianli; Zhang, Huigang; Liu, Jinyun
Abstract : We developed a unique mesostructured iron sulfide comprising nanoparticles embedded within a nanoneedles-assembled nanotube to form a "caterpillar with eggs" structure that displayed high lithium-storage performance. Abstract : Emerging anodes are important for high energy-density lithium-ion batteries. Here, we present a mesostructured FeS2 comprising nanoparticles embedded in a nanoneedle-assembled nanotube to form a novel "caterpillar with eggs" (CWE) structure. The voids alleviated the volumetric change upon charge–discharge; the nanoneedles-assembled shell provided rapid transport pathways for ions and electrons. The FeS2 anode exhibited a high capacity of 805.1 mA h g −1 after 500 cycles at 2 A g −1 . When cycling at −10 °C and 45 °C, the anode provided capacities of 754.5 and 744.4 mA h g −1 after 100 cycles at 1 A g −1, respectively. This good electrochemical performance will enable our special design to find broad applications for developing high-performance energy-storage systems.